2018
DOI: 10.3847/1538-4357/aad9f8
|View full text |Cite
|
Sign up to set email alerts
|

A Census of Ionized Gas Outflows in Type 1 AGNs: Gas Outflows in AGNs. V.

Abstract: We present a systematic study of ionized gas outflows based on the velocity shift and dispersion of the [O III] λ5007Å emission line, using a sample of ∼ 5000 Type 1 AGNs at z < 0.3 selected from Sloan Digital Sky Survey. This analysis is supplemented by the gas kinematics of Type 2 AGNs from Woo et al. (2016). For the majority of Type 1 AGNs (i.e., ∼ 89%), the [O III] line profile is best represented by a double Gaussian model, presenting the kinematic signature of the non-virial motion. Blueshifted [O III] i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
90
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(107 citation statements)
references
References 75 publications
17
90
0
Order By: Relevance
“…Our findings are in qualitative agreement with the re-sults presented by Rakshit & Woo (2018) for a large sample of low-redshift AGN selected from the SDSS DR12 catalog (z<0.3), where blueshifted [O iii] outflows are more frequently detected than redshifted ones by a factor of 3.6 in type 1 AGN, while the ratio between blueshifted and redshifted [O iii] is only 1.08 for type 2 AGN due to projection and orientation effects. Overall, the outflow fractions found by Rakshit & Woo (2018) are larger than the fractions we find here for all AGN types. This is most likely due to the identification and limits imposed by the different outflow detection methods, as well as the inherent [O iii] luminosity of the different samples.…”
Section: Outflow Fractionsupporting
confidence: 91%
“…Our findings are in qualitative agreement with the re-sults presented by Rakshit & Woo (2018) for a large sample of low-redshift AGN selected from the SDSS DR12 catalog (z<0.3), where blueshifted [O iii] outflows are more frequently detected than redshifted ones by a factor of 3.6 in type 1 AGN, while the ratio between blueshifted and redshifted [O iii] is only 1.08 for type 2 AGN due to projection and orientation effects. Overall, the outflow fractions found by Rakshit & Woo (2018) are larger than the fractions we find here for all AGN types. This is most likely due to the identification and limits imposed by the different outflow detection methods, as well as the inherent [O iii] luminosity of the different samples.…”
Section: Outflow Fractionsupporting
confidence: 91%
“…In addition to confirming a broad correlation between σ [O III] and σ * , they found that objects with non-gravitational outflow components do not follow a linear correlation, and instead have higher σ [O III] /σ * ratios for higher σ * . In a subsequent study, Rakshit & Woo (2018) found similar results to Woo et al (2016) as a function of stellar velocity dispersion σ * using three methods: (1) fitting a single-Gaussian model, (2) measuring the flux-weighted dispersion of the full line profile, and (3) fitting a double-Gaussian model. The fluxweighted dispersion is calculated using the same method as Woo et al (2016), which calculated the second-order Gaussian moment of the sum of the full (core+blue wing) best-fit model to [O III]λ5007.…”
Section: [O Iii]λ5007 As a Surrogate For Stellar Velocity Dispersionsupporting
confidence: 74%
“…It appears there is a large 15 When we refer to ∆v or σ of a Gaussian component (∆v broad/narrow , σ broad/narrow ), it is directly converted as the model center and FWHM/2.355 respectively, whereas those of the total profile (∆v total , σ total ) are calculated as the luminosity weighted 1st or 2nd moments of the model unless specified otherwise. (e.g., Mullaney et al 2013;Woo et al 2016;Rakshit & Woo 2018), but we test whether the [O III] kinematics of Hot DOGs indicate higher σ [O III],broad values at their high luminosities. In Figure 6 Figure 6, or from the literature (e.g., Woo et al 2016;Rakshit & Woo 2018).…”
Section: Extinction Measuresmentioning
confidence: 99%